If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2 = 9.5 Reorder the terms: 2 + 3x = 9.5 Solving 2 + 3x = 9.5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 3x = 9.5 + -2 Combine like terms: 2 + -2 = 0 0 + 3x = 9.5 + -2 3x = 9.5 + -2 Combine like terms: 9.5 + -2 = 7.5 3x = 7.5 Divide each side by '3'. x = 2.5 Simplifying x = 2.5
| 3x-12-5x=6x+8-10x | | 4x+8+6x=12 | | r-11/3=7 | | 3f=99 | | f(9)=9x+1 | | an=3(5)n-1 | | 8x-7=x+9 | | x^7-41=235 | | 2x^2+2x-576=0 | | -13=y-94 | | 10n^2=20-8n | | -6/16 | | (1x+6x)=14-x | | 5x+3x=90 | | -2*-1/3 | | ins(x)=90 | | 4r=-12+28 | | -2z-9=2z-5 | | 2j=-60*5 | | -2×-1/3 | | 3/7*a=12 | | 35=1x+16 | | 6(x+6)=102 | | 1/10y=7/5 | | 35=1x+35 | | 5.37+27.7+4= | | 55n=-55 | | C-46=68 | | .03y+1=4.3 | | -6/16v | | -x+5=-2x+-4x | | 6p^2=-9+9p |